Research on the Influence of SST in Different Regions on the Interannual Variability of Winter Fog Days over Eastern China - Qisheng CEN; Peng LIU (Gaoyuan qixiang)
Based on observational data， it is evident that fog occurrence in Eastern China is notably higher during winter compared to other months.Spatial analysis of climatological statistics reveals a distinct heterogeneity， dividing Eastern China into northern and southern regions based on fog day patterns.Furthermore， winter can be subdivided into early （November and December） and late （January and February） periods， characterized by varying trends in fog occurrence and interregional correlations.Examining the relationship between sea surface temperature （SST） and fog days across both southern and northern China throughout winter， significant influences emerge.During early winter， fog days in both regions are markedly impacted by SST anomalies in the tropical Pacific.Conversely， in late winter， while the north Atlantic SST exerts a considerable influence on fog days in northern China， southern China continues to be strongly affected by tropical Pacific SST.Analyzing atmospheric circulation patterns reveals distinct mechanisms driving fog occurrences in different seasons.In early winter， warm SST anomalies in the tropical Pacific drive northward movement of the Western North Pacific Subtropical High， resulting in anticyclonic anomalies over northern Japan and weakened Siberian High， leading to increased fog days in both southern and northern areas of Eastern China.Conversely， in late winter， weakened influence from the tropical Pacific shifts the anomalous southerly winds only over southern China， while the north Atlantic SST anomalies induce anomalous southeasterly winds over northern areas， enhancing moisture transport from the north Pacific， with relatively stable atmospheric structure， thus significantly increasing fog days over northern China.